2003
DOI: 10.1034/j.1600-051x.2003.20077.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of two potassium nitrate bioadhesive gels (5% and 10%) in the treatment of dentine hypersensitivity. A randomised clinical trial

Abstract: A greater reduction of DH after ES was observed after 48 h of treatment in the NK10% group (35.8%) compared to the NK5% group and placebo group (11.8% and 13.4%, respectively). This difference increased significantly at 96 h (p=0.003). No significant differences were observed for the other variables. These preliminary results may support the usefulness of an NK 10% gel to reduce the DH after stimulation with a blast of air during the first 4 days of its appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
3
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 16 publications
3
36
3
4
Order By: Relevance
“…Chemical agents that have been suggested included strontium chloride, sodium fluoride, formalin solution 9) , ferric oxalate 10) , calcium hydroxide, stannous hydroxide, calcium oxalate, ferric phosphate 11) , potassium nitrate 12) , visible light-cured materials 13) , and fluoride varnishes 14) , while physical agents included Nd:YAG laser 15) and GaAlAs laser 16) . Although these materials yielded promising results, their therapeutic effects were relatively short-lived or decreased with time because these agents could be gradually removed by daily toothbrushing or acidic beverage drinking.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical agents that have been suggested included strontium chloride, sodium fluoride, formalin solution 9) , ferric oxalate 10) , calcium hydroxide, stannous hydroxide, calcium oxalate, ferric phosphate 11) , potassium nitrate 12) , visible light-cured materials 13) , and fluoride varnishes 14) , while physical agents included Nd:YAG laser 15) and GaAlAs laser 16) . Although these materials yielded promising results, their therapeutic effects were relatively short-lived or decreased with time because these agents could be gradually removed by daily toothbrushing or acidic beverage drinking.…”
Section: Introductionmentioning
confidence: 99%
“…A clinical study using 5% potassium nitrate solution also found no DH reduction 13) . However, a study using 10% potassium nitrate gel reported a 35% reduction in DH within 48-96 h 14) and another study using 35% potassium nitrate gel reported a 91% reduction in DH immediately after application 15) . A wide range of agents have been shown to relieve DH by occluding the dentinal tubules, thus reducing stimulus-evoked fluid flow 10) .…”
Section: Introductionmentioning
confidence: 99%
“…Subjects who had undertaken treatment with any product that could influence the DH of the patient in the 30 days prior to baseline were excluded. 26 In addition, subjects were also excluded if they were allergic to ingredients used in the study or exhibited any gross oral pathology, eating disorders, chronic disease, pregnancy and lactation, acute myocardial infarction within the past six months, use of pacemaker, uncontrolled metabolic disease, major psychiatric disorder, heavy smoking or alcohol abuse, any systemic disease or any disease requiring repeated or regular analgesia, anti-inflammatory drugs, or antihistamines. 25 …”
Section: Inclusion-exclusion Criteriamentioning
confidence: 99%